2010
DOI: 10.1038/jid.2009.253
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Fibroblasts Promote the Migration of Dendritic Cells

Abstract: Migration of dendritic cells (DCs) from skin to lymph nodes on activation is an essential step in the initiation of an adequate immune response. The dermal microenvironment including stromal cells and their soluble factors might be involved in the regulation of DC migration. To focus on the role of dermal fibroblasts, we studied whether interaction of DCs with fibroblasts promotes the migration of DCs. DCs were co-cultured with resting fibroblasts or with tumor necrosis factor (TNF)alpha/IL-1beta-activated fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 49 publications
4
61
0
1
Order By: Relevance
“…Cytokines are released by fibroblasts in patterns that distinguish fibroblasts from different anatomic sites and disease states (33,34,60). These studies validate and extend recent in vitro studies suggesting that cultured skin fibroblasts stimulated with TNF/IL-1 can promote DC migration or increase the maturation of LPS-stimulated DCs by a complex feedback mechanism involving IL-1β secreted from DCs (62,63). Our data now demonstrate that in physiologic models, fibroblast Itgb8 is required for lung DC migration.…”
Section: Discussionsupporting
confidence: 75%
“…Cytokines are released by fibroblasts in patterns that distinguish fibroblasts from different anatomic sites and disease states (33,34,60). These studies validate and extend recent in vitro studies suggesting that cultured skin fibroblasts stimulated with TNF/IL-1 can promote DC migration or increase the maturation of LPS-stimulated DCs by a complex feedback mechanism involving IL-1β secreted from DCs (62,63). Our data now demonstrate that in physiologic models, fibroblast Itgb8 is required for lung DC migration.…”
Section: Discussionsupporting
confidence: 75%
“…3 Morphologic analysis and high expression of CD1a and CD11c were parameters for quality and purity of DC preparations. An immature phenotype of DCs was verified by low expression of CD80, CD83, CD86, and HLA-DR.…”
Section: Cell Preparation and Culture Conditionsmentioning
confidence: 99%
“…Recently, we demonstrated an interaction of DCs and fibroblasts, resulting in enhanced migration of DCs. 3 Several groups reported the effect of stromal cells on the regulation of DC functions under steady-state as well as inflammatory conditions. 4,5 Renkl et al 6 and Termeer et al 7 showed that maturation and differentiation of DCs are regulated by the extracellular matrix components hyaluronic acid and osteopontin.…”
Section: Introductionmentioning
confidence: 99%
“…We also examined primary human foreskin fibroblasts (HFFs), which is a cell type permissive to productive HCMV replication that has also been shown to play an important role in regulating a variety of immune functions (26)(27)(28). In three independent replicate experiments, both MDMs and MDDCs significantly upregulated hIL-10 in response to cmvIL-10 treatment, whereas hIL-10 remained below detectable limits before and after cmvIL-10 treatment of CD4 ϩ and CD8 ϩ T cells and HFFs.…”
Section: Cmvil-10 Upregulates Secretion Of Hil-10 Protein By Cd14mentioning
confidence: 99%